A High Activity Level Is Required for Augmented Muscle Capillarization in Older Women. Issue 5 (May 2021) - Gliemann, Lasse; Rytter, Nicolai; Yujia, Liu; Tamariz-Ellemann, Andrea; Carter, Howard; Hellsten, Ylva
ABSTRACT: Purpose: This study aimed to evaluate the influence of lifelong regular physical activity on skeletal muscle capillarization in women. Methods: Postmenopausal women, 61±4 yr old, were divided according to self-reported physical activity level over the past 20 yrs: sedentary (SED; n = 14), moderately active (MOD; n = 12), and very active (VERY; n = 15). Leg blood flow (LBF) was determined by ultrasound Doppler, and blood samples were drawn from the femoral artery and vein for calculation of leg oxygen uptake (LVO2 ) at rest and during one-legged knee extensor exercise. A skeletal muscle biopsy was obtained from the vastus lateralis and analyzed for capillarization and vascular endothelial growth factor (VEGF) and mitochondrial OXPHOS proteins. Platelets were isolated from venous blood and analyzed for VEGF content and effect on endothelial cell proliferation. Results: The exercise-induced rise in LBF and LVO2 was faster ( P = 0.008) in VERY compared with SED and MOD. Steady-state LBF and LVO2 were lower ( P < 0.04) in MOD and VERY compared with SED. Capillary–fiber ratio and capillary density were greater ( P < 0.03) in VERY (1.65 ± 0.48 and 409.3 ± 57.5) compared with MOD (1.30 ± 0.19 and 365.0 ± 40.2) and SED (1.30 ± 0.30 and 356.2 ± 66.3). Skeletal muscle VEGF and OXPHOS complexes I, II, and V were 1.6-fold and 1.25-fold ( P < 0.01) higher, respectively, in VERY compared with SED. Platelets from all groups induced an approximately nine-fold ( P < 0.001) increase in endothelial cell proliferation. Conclusion: A very active lifestyle is associated with superior skeletal muscle exercise hemodynamics and greater potential for oxygen extraction concurrent with a higher skeletal muscle capillarization and mitochondrial capacity. Abstract : Supplemental digital content is available in the text.